Persepsi Pedagang Muslim Dikabupaten Sarolangun terhadap Urgensi Labelisasi Halal Produk - Nz, Naza Nazira; Yusuf, Maulana (Lembaga Yasin AlSys, 2026)
Halal labeling is an important aspect in providing assurance of product halalness for Muslim consumers, especially in culinary businesses that are directly related to people’s consumption needs. This study aims to analyze the perceptions of Muslim traders in Sarolangun Regency regarding the urgency of halal products and to identify the factors influencing their interest in applying halal labels to the products they trade. This study used a qualitative approach with a descriptive field design. The research subjects were Muslim traders in Sarolangun Regency, Jambi Province, who were selected based on their connection with food businesses. Data were collected through observation, interviews, and documentation, and were then analyzed through the stages of data collection, data reduction, data display, and conclusion drawing. The results showed that Muslim traders’ perceptions of halal labeling were positive in religious and moral terms but were not yet strong in administrative and implementative terms. The factors influencing these perceptions included knowledge, socialization, economic conditions, religious values, and consumer demand. Thus, this study emphasizes the importance of strengthening halal literacy among small traders so that religious and moral understanding can be followed by administrative readiness in implementing halal labeling. The implications of this study suggest that the government and relevant institutions should strengthen education, assistance, and ease of halal certification for culinary business actors.